2019
DOI: 10.1186/s12879-019-4293-8
|View full text |Cite
|
Sign up to set email alerts
|

Retention in care and adherence to HIV and AIDS treatment in Anambra State Nigeria

Abstract: Background Retaining patients on antiretroviral treatment in care is critical to sustaining the 90:90:90 vision. Nigeria has made some progress in placing HIV-positive patients on treatment. In an effort to increase access to treatment, ART decentralization has been implemented in the country. This is aimed at strengthening lower level health facilities to provide comprehensive antiretroviral treatment. We determined the level of retention and adherence to treatment as well as the associated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 34 publications
(33 reference statements)
7
26
0
2
Order By: Relevance
“…Marital status for both men and women was signi cantly associated with retention in HIV care in our study. Our ndings are similar to those reported by Umeokonkwo et al (2019) in Anambra state in Nigeria in which marital status was a signi cant predictor of retention (30). Being married, or having a spouse provides a source of psychological and emotional support which improves retention in care compared to those who are single and not in a relationship.…”
Section: Socio-demographics and Disease Characteristicssupporting
confidence: 88%
“…Marital status for both men and women was signi cantly associated with retention in HIV care in our study. Our ndings are similar to those reported by Umeokonkwo et al (2019) in Anambra state in Nigeria in which marital status was a signi cant predictor of retention (30). Being married, or having a spouse provides a source of psychological and emotional support which improves retention in care compared to those who are single and not in a relationship.…”
Section: Socio-demographics and Disease Characteristicssupporting
confidence: 88%
“…26,27 Additional factors showed that the kind of attention the healthcare provider offered, improved quality of HIV services, and the use of western medicine were pivotal to ART adherence. This was critical as the use of "alternative HIV treatment options" mainly traditional concoctions, holy water, as well as prayers as a cure for HIV had been reported from previous studies; [27][28][29][30]31 and such beliefs showed the growing demand for improved healthcare services, as well as addressing societal and culture barriers of ART. While the findings of this study are valid, they ought to be interpreted with caution due to the following limitations: a) the study was only limited to Al-Sabah Children's Hospital and cannot be generalizable to other health facility, b) also a small sample size of 126 caregiver-child pair was used, c) the use of caregiver self-report may have overrated ART adherence due to recall bias as well as attempt to impress the interviewer and healthcare providers, d) ART adherence was assessed based on missed doses with no regard of correct timing of medication, e) caregiver self-reported adherence relied on their giving rightful information, f) the reported past 7 days of ART adherence was a short time and may not have correlated well with annual adherence levels, and g) the study only used interview data.…”
Section: Discussionmentioning
confidence: 99%
“…The total adherence was measured by average all the adherence percentage of every follow-up. Participants with≥95% adherence were classified as having "good adherence" while those that took below 95% of their ART were classified as having poor adherence [22].…”
Section: Methodsmentioning
confidence: 99%